2002
DOI: 10.1046/j.1365-3180.2002.00281.x
|View full text |Cite
|
Sign up to set email alerts
|

The persistence of seeds of 16 weed species over six years in two arable fields

Abstract: Summary Two experiments have investigated the persistence of 16 arable, annual broad‐leaved weed species over 6 years in a silty loam and a clay soil. Small plastic beads were included as an ‘inert’ comparison. Seeds were broadcast in October on to plots at the start of the experiment, and these were either tine cultivated or ploughed annually thereafter. Plots were sown with either spring or winter wheat. As far as possible, weed seeding was prevented each year. For some species, the seed decline appeared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 19 publications
3
66
3
Order By: Relevance
“…However, long-term studies also indicated that after 3 to 4 yr, seed mortality in undisturbed, buried seeds becomes negligible and a small fraction of volunteer winter B. napus seed readily persisted for up to one decade (Lutman et al 2003). When compared with other common weed species in the United Kingdom, the initial seed bank decline rates of volunteer winter B. napus were among the most rapid (Lutman et al 2002;Lutman et al 2005). Dormancy * Neither domesticated B. napus nor domesticated B. rapa exhibit primary seed dormancy at maturity (Pekrun et al 1998b;Gulden et al 2004a).…”
Section: Historymentioning
confidence: 99%
“…However, long-term studies also indicated that after 3 to 4 yr, seed mortality in undisturbed, buried seeds becomes negligible and a small fraction of volunteer winter B. napus seed readily persisted for up to one decade (Lutman et al 2003). When compared with other common weed species in the United Kingdom, the initial seed bank decline rates of volunteer winter B. napus were among the most rapid (Lutman et al 2002;Lutman et al 2005). Dormancy * Neither domesticated B. napus nor domesticated B. rapa exhibit primary seed dormancy at maturity (Pekrun et al 1998b;Gulden et al 2004a).…”
Section: Historymentioning
confidence: 99%
“…As a consequence most of the shed seeds germinate within two years and fail to enter the seed bank, if appropriate germination conditions occur Hails et al, 1997;Lutman et al, 2002Lutman et al, , 2004Norris and Sweet, 2002;Roller et al, 2003). However, owing to environmental factors, some of the buried seeds can develop secondary dormancy and remain dormant for several years (Gulden, 2003;Gulden et al, 2003b;Lutman et al, 2004).…”
Section: Seed Dispersal In Timementioning
confidence: 99%
“…The duration of the persistence varies with the cultivar and the conditions of burial, with higher persistence at depth than near the surface, in heavy soils than in lighter ones, and in undisturbed environments (Chadoeuf et al, 1998;Gruber et al, 2004;Gulden, 2003;López-Granados and Lutman, 1998;Lutman et al, 2002Lutman et al, , 2004Momoh et al, 2002;Pekrun et al, 1997b;Pekrun et al, 2003;Pessel et al, 2001;Roller et al, 2003;Simard et al, 2002;Squire et al, 2003). Under normal cropping conditions ca.…”
Section: Seed Dispersal In Timementioning
confidence: 99%
“…In a 4-year cropping rotation of oaten hay/field pea/wheat/barley, rigid ryegrass (Lolium rigidum) seedbank declined by 86% after oaten hay in year 1 (Kleemann et al, 2016). In a seed persistence study, Lutman et al (2002) found that seed loss rates of 16 weed species over 6 years varied from 8 to 58%.…”
Section: Weed Seedbank Dynamicsmentioning
confidence: 99%